Factors associated with colorectal cancer screening in a peer-counseling intervention study in partnership with African American churches - Maxwell, Annette E. (Prev Med Rep, 2020)
Colorectal cancer (CRC) mortality is 47% higher in African American men and 34% higher in African American women compared to non-Hispanic white men and women. This analysis assessed factors associated with CRC screening among 163 African American participants of a peer-counseling intervention study (2016–2018). In a one-group pre/post-test pilot study, trained Community Health Advisors (CHAs) at 9 African American churches in Los Angeles (LA) promoted CRC screening via one-on-one counseling, print materials and telephone reminder calls. Participants completed telephone surveys 3–6 months after the intervention. We fit bivariate and multivariate mixed effects logistic regression models to assess correlates, including participants’ demographic characteristics, access to care, cancer-related knowledge and attitudes and receipt of CHA counseling of (1) discussion of CRC screening with provider and (2) receipt of CRC screening during follow-up. After controlling for gender and education, receipt of CHA counseling (OR 3.77) was significantly associated with discussing CRC screening with a provider during follow-up but not with CRC screening. Instead, a routine check-up in the past 12 months (OR 4.47) and discussion of CRC screening with a provider (OR 3.07) were significantly associated with CRC screening during follow-up. Residence in South LA (OR 0.38) was significantly associated with lack of CRC screening. Findings confirm the important role of health care providers and suggest that residence in South LA constitutes an additional barrier to CRC screening. Further research and additional resources are needed to address disparities in the uptake of CRC screening among African Americans, especially in South LA.